How ideas matter in public policy: a review of concepts, mechanisms, and methods - Marij Swinkels (International Review of Public Policy)
The recent ideational turn in political science and public administration implies that ideas matter. Ideas are an essential explanatory concept for understanding policy changes and decision-making processes. The aim of the paper is to specify how ideas matter as a variable in public policy research, providing students and scholars of public policy with a stock take of the current state-of-the-art literature on ideas in political science and public administration. The paper first identifies three approaches to ideas as a variable in the policy process. It then discusses where ideas come from and the dynamics and drivers of ideational change to shed light on the ideational mechanisms underpinning policy processes. Furthermore, it taps into different research methods that can be used to study ideas. Finally, the paper concludes with five lessons for future research endeavours on the study of ideas in public policy.